The determinants of Islamophobia: An empirical analysis of the Swiss minaret referendum - Olga Orlanski; Günther G. Schulze (University of Freiburg, Department of International Economic Policy (iep), 2018)
We analyze the determinants of Islamophobia using the only nation-wide anti-Islam referendum ever, which was held in Switzerland in 2009 and led to the prohibition of minarets. We find economic, environmental, and cultural factors as well as the presence of Muslims to determine voting behavior. Approval rates for the bill rise with unemployment and decrease with education, income, and the attractiveness of the location. Approval is higher in rural areas, in municipalities with a higher share of men, and in the Italian and German speaking parts of Switzerland. It is higher in municipalities with a higher share of Muslims, which strongly supports the "religious threat" hypothesis. We compare the voting behavior in the minaret referendum with the referendum "for democratic naturalizations", held in 2008, in order to disentangle determinants of Islamophobia from those of xenophobia. We show that our results are robust to the estimation with ecological inference.
Keywords: 330; Referendum; Minaret referendum; Islamophobia; Xenophobia; Ecological Fallacy